Joint Bidding, Governance and Public Procurement Costs : A Case of Road Projects - Estache, Antonio; Iimi, Atsushi (2012)
To utilize public resources efficiently, it is important to take advantage of competition in public procurement auctions to the maximum extent. Joint bidding is a common practice that potentially facilitates competition. By pooling financial and experiential resources, more firms are expected to enter the market, but it will also directly reduce competition if more than one bidder who is solely qualified makes a coalition. In theory joint bidding may or may not be beneficial to auctioneers, depending on the model. The paper empirically examines the impacts of joint bidding on firms' entry as well as bidding behaviour, using data on public road projects in developing countries. It shows that coalitional bids, in particular by local firms, would be competitive, but foreign joint ventures would undermine competition. It is also found that good governance can encourage firms' entry into the tendering and facilitate joint bidding practices.